Edge-mediated effects of forest fragments on the trophic structure of stream fish - de Paula Ferreira, Cristiane; Casatti, Lilian [UNESP]; Zeni, Jaquelini O. [UNESP]; Ceneviva-Bastos, Mônica [UNESP] (Springer Nature, 2015)
The aquatic communities of headwater streams are highly influenced by the surrounding matrix. The edge effects of forest fragments are known to influence terrestrial communities; however, their influence on aquatic communities remains poorly understood. The aim of this study was to investigate whether and how edge effects can influence stream environmental variables and fish trophic structure. We sampled stream reaches located within forest fragments (192–2480 ha) and stream reaches located on the forest edge during wet and dry periods to describe local habitat variables and fish trophic structure. We found high dissimilarity in the trophic structure (>60%) between stream positions and between seasons. Aquatic invertivores contributed to the majority of the observed dissimilarity. Omnivores and algivores were more abundant on edge reaches and were notably associated with high water temperature. Herbivores and terrestrial invertivores were more abundant in the interior reaches mostly during the wet season and were associated with high dissolved oxygen. The scarcity of riparian forest cover on the edge reaches not only caused physical changes but also influenced the fish trophic structure, therefore providing evidence of edge-mediated effects.
Keywords: Agroecosystems; Conservation; Edge effect; Fish feeding; Riparian vegetation; Trophic guilds